Tackling burnout in Australian doctors by blending a web-based cognitive-behavioural therapy program with telehealth psychological support – protocol for a three-arm randomised-controlled trial - M.J. Coleshill; M.J. Black; K. Luck; K. Willis; N. Smallwood; H. Stephens; T. Gillings; L. Fraser; M. Putland; L. Kampel; A.M. Martin; N.F. Praharso; et al. (Contemporary Clinical Trials Communications)
Background: Burnout has received limited attention in treatment programs, despite high prevalence among health professionals and the threat burnout places upon the mental health and the long-term sustainability of the Australian healthcare system. As part of The Essential Network (TEN), a blended care mental health support service for Australian health professionals, we developed Navigating Burnout – a digital cognitive-behavioural therapy program for health professional burnout. This three-arm randomised-controlled trial (RCT) will examine the effectiveness, acceptability, and cost-effectiveness of Navigating Burnout in both blended care and digital formats in reducing burnout among doctors. Methods: Doctors (n = 207) with burnout will be randomised to (1) a blended version of Navigating Burnout combining digital resources with five fortnightly telehealth sessions with a clinical psychologist, (2) a digital-only version of Navigating Burnout, or (3) self-care psychoeducation as an active attention control. Burnout, psychosocial wellbeing, workforce engagement and attrition, and service acceptability will be measured at baseline, post-treatment, and 3 months post-treatment. Results: At 3 months post-treatment, we hypothesise reductions in burnout across both treatment arms, with the strongest effect in the blended care arm. Similar trends are expected for psychosocial and occupational outcomes. High service acceptability across both blended care and digital-only versions of Navigating Burnout is also anticipated. Conclusions: With this evidence, Navigating Burnout may be incorporated into TEN's person-to-person components. Further, by demonstrating the effectiveness of blended care for burnout, Navigating Burnout may provide a crucially needed service for Australian doctors and replicable model of care for other organisations and support services.